Apical instrumentation in endodontic therapy - Darliana, Kurniasri; Sukartini, Endang (Padjadjaran Journal of Dentistry, 2007)
Cleaning and shaping of the root canal as the foundation for successful endodontic therapy. Cleaning of the root canal as the removal of all the contents of the root canal systems before and during shaping. Mechanical cleaning as the most important part of the root canal therapy. Instrumentation of the apical region has long been considered to be an essential component in the cleaning and shaping process. The apical area as the critical zone for instrumentation. The apical portion of the root canal system can retain microorganisms that could potentially cause periradicular inflammation. The nickel-titanium rotary instrumentation system to facilitate the cleaning and shaping process. Larger instrumentation sizes not only allow proper irrigation but also significantly decrease remaining bacteria in the canal system. How the larger apical sizes preparation must be achieved to clinical success. This paper will describe the major factors impacting the selection of final apical size, the factors are the anatomy of the apical constriction, root canal diameter, apical instrumentation, and bacteria in dentin tubuli.